The future of health and fitness : a plan for getting Europe active by 2025 - Breuer, Christoph, ....- (Nijmegen : Black Box Publishers, 2014)
The European Union's population of over 500 million people has become more sedentary and less physically active. The Euro barometer study on physical activity and sport has shown that 60% of the population is getting little or no exercise to be beneficial for health. In the EU 52% of the adult population is now overweight and 17% are obese. It is in this context of this immense challenge to get people exercise more and eat healthier that EuropeActive (former European Health & Fitness Association - EHFA), and such the European Health & Fitness sector, now "raises the bar" and announces its commitment to get more Europeans active by 2025. This hardcover book of 218 pages is a unique collection of contributions of 13 experts, like Prof Dr Willem van Mechelen, Prof Dr Alfonso Jemenez and Prof Dr Christoph Breuer, on the scientific evidence around the medical, psychological and economic benefits of physical activity, exercise and fitness for all ages. The book includes many recommendations on how to get Europeans to become more active. The target audience of the book is broad: health club operators, scientists, students, fitness professionals, policymakers, and many more.